Cultivar Differences in Root Nitrogen Uptake Ability of Maize Hybrids - Li, Qiang; Wu, Yawei; Chen, Wei; Jin, Rong; Kong, Fanlei; Ke, Yongpei; Shi, Haichun; Yuan, Jichao (Frontiers in Plant Science, 2017)
Although, considerable differences in root size in response to nitrogen (N) application among crop species and cultivars have been widely reported, there has been limited focus on the differences in root N uptake ability. In this study, two maize (Zea mays L.) hybrids, Zhenghong 311 (ZH 311, N-efficient) and Xianyu 508 (XY 508, N-inefficient), were used to compare differences in root N uptake ability. The two cultivars were grown in field pots Experiment I (Exp. I) and hydroponic cultures Experiment II (Exp. II) supplemented with different concentrations of N fertilizer. In both experiments, the levels of accumulated N were higher in ZH 311 than in XY 508 under low- and high-N supply, and the increment in accumulated N was greater under N deficiency. The maximum N uptake rate (Vm) and average N uptake rate (Va) in Exp. I, the root N kinetic parameter maximum uptake rate (Vmax) per fresh weight (FW) and Vmax per plant in Exp. II, and the root N uptake rate in both experiments were significantly higher for ZH 311 than for XY 508. In contrast, the root-to-shoot N ratio in both experiments and the root N kinetic parameter Michaelis constant (Km) in in Exp. II were markedly higher in XY 508 than in ZH 311, particularly under N-deficient conditions. Higher root N kinetic parameters Vmax per FW and Vmax per plant and lower Km values contributed to higher N affinity and uptake potential, more coordinated N distribution in the root and shoot, and higher root N uptake rates throughout the growth stages, thus enhancing the N accumulation and yield of the N-efficient maize cultivar. We conclude that the N uptake ability of roots in the N-efficient cultivar ZH 311 is significantly greater than that in the N-inefficient cultivar XY 508, and that this advantage is more pronounced under N-deficient conditions. The efficient N acquisition in ZH 311 is due to higher N uptake rate per root FW under optimal N conditions and the comprehensive effects of root size and N uptake rate per root FW under N deficiency.